2008
DOI: 10.2516/ogst:2007080
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Crudes: A Comparative Study of SARA Fractions from a Modified HPLC Separation Technique

Abstract: Résumé -Pétroles bruts canadiens : étude comparative des fractions SARA à partir d'une technique de séparation HPLC modifiée -Ces dernières années, une réduction mondiale des réserves de pétrole conventionnel pouvant être exploitées a amené à une augmentation des activités d'exploration et de production des pétroles bruts les plus lourds. Au Canada, il a été demandé aux unités de valorisation d'étudier les pétroles lourds et les bitumes provenant des sables bitumineux, plus accessibles mais plus difficiles à e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 18 publications
1
27
0
3
Order By: Relevance
“…1 Oil fractions oxidation during routine isolation have been discussed before; 16,71 existence of oxidized forms in Athabasca asphaltenes has also been published based on XPS analysis. 72 The larger aggregation tendency for solvent extracted asphaltenes discussed in the preceding paragraphs, might in part derive from their extended oxidation occurring during additional exposition to air. Since most standard asphaltenes isolation methods 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 routinely practiced during many decades do not contemplate inert atmospheres, 6-13 the present results attempt to make a point in this regard.…”
Section: Preliminary Insights Into Chemical Functionalities Of Selectmentioning
confidence: 98%
“…1 Oil fractions oxidation during routine isolation have been discussed before; 16,71 existence of oxidized forms in Athabasca asphaltenes has also been published based on XPS analysis. 72 The larger aggregation tendency for solvent extracted asphaltenes discussed in the preceding paragraphs, might in part derive from their extended oxidation occurring during additional exposition to air. Since most standard asphaltenes isolation methods 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 routinely practiced during many decades do not contemplate inert atmospheres, 6-13 the present results attempt to make a point in this regard.…”
Section: Preliminary Insights Into Chemical Functionalities Of Selectmentioning
confidence: 98%
“…For sulfur existing condition, J. Woods suggested that more thiophenic sulfur than thiols one by HPLC technique [30], so only At-S was selected from D&G model. R-benzo-thino-1s…”
Section: Establishment Of Molecular Modelsmentioning
confidence: 99%
“…The hydrocarbons that contain heteroatoms could vary from very simple one such as thiophene to very complex mixtures such as asphaltenes for which the structure is not well understood, but known to contain sulfur, oxygen and nitrogen at different levels, in addition to carbon and hydrogen (Buenrostro-Gonzalez et al, 2002;Woods et al, 2008).…”
Section: Non-hydrocarbonsmentioning
confidence: 99%